Analysis of the Effect of Fraud Pentagon Factors on Fraudulent Financial Statement with Audit Committee as Moderating Variable - Dewi, Krisna; Anisykurlillah, Indah (Universitas Negeri Semarang, 2021)
This study aims to analyze the effect of fraud pentagon on fraudulent financial statements with audit committee as moderating variable. The population of this study was the property, real estate, and construction companies listed on the Indonesia Stock Exchange during 2016-2018. The sampling technique used purposive sampling and obtained 52 companies with 156 units of analysis. The data were analyzed using logistic regression analysis by IBM SPSS Ver.26. The results showed that company growth had a positive effect on fraudulent financial statements. Meanwhile, the effectiveness of supervision, quality of external auditors, the experience of directors, and CEO duality did not affect fraudulent financial statements. Audit committee significantly moderated the effect of company growth, the effectiveness of supervision, and the experience of directors on fraudulent financial statements. However, audit committee did not moderate the effect of quality of external auditors and CEO duality on fraudulent financial statements. This study concludes that the fraudulent financial statements will be higher when the company growth is higher. Audit committee weakens the effect of company growth, the effectiveness of supervision, and the experience of directors on fraudulent financial statements. Keywords: Fraudulent Financial Statement; Fraud Pentagon; Audit Committee